BANKRUPTCY PREDICTION WITH THE ALTMAN Z-SCORE, SPRINGATE, ZMIJEWSKI, AND GROVER MODELS - Reza, Muhammad Jamil; Pagalung, Gagaring; Damayanti, Ratna Ayu (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2023)
Purpose – This study aims to predict bankruptcy towards food and beverage subsector and finding the most accurate analysis model among the Altman Z-Score, Springate, Zmijewski, and Grover Design/methodology/approach – This analysis uses quantitative descriptive method using Ms. Excel, then performed Kruskal Wallis and accuracy test using IBM-SPSS Findings – The results by three-year average calculation using Altman Z-Score model shows that 2 out of 21 companies have the potential to go bankrupt, Springate model has 9 out of 21 companies, Zmijewski model has 3 out of 21 companies, and based on Grover model there are 2 out of 21 companies. The results of the hypothesis test showed that there were differences between the models and the Zmijewski model is the most accurate for food and beverage subsector companies. Originality – This study uses the most accurate analysis model among the Altman Z-Score, Springate, Zmijewski, and Grover by using 2017-2019 financial report data published on Indonesia Stock Exchange (IDX) Keywords: Bankruptcy, Altman Z-Score, Springate, Zmijewski, Grover Paper Type Research Result